Exploratory data analysis with MATLAB - Martinez, Wendy L.; Martinez, Angel R. (Computer science and data analysis series., 2005)
Presents the methods of Exploratory Data Analysis (EDA) from a computational perspective. This book uses MATLAB code and algorithm descriptions to provide techniques for finding patterns and structure in data. It places the tools that are needed to implement EDA theory at the fingertips of applied mathematicians, and computer scientists.